2012
DOI: 10.1021/es300020e
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating the Effects of Bioremediation on Genotoxicity of Polycyclic Aromatic Hydrocarbon-Contaminated Soil Using Genetically Engineered, Higher Eukaryotic Cell Lines

Abstract: Bioremediation is one of the commonly applied remediation strategies at sites contaminated with polycyclic aromatic hydrocarbons (PAHs). However, remediation goals are typically based on removal of the target contaminants rather than on broader measures related to health risks. We investigated changes in the toxicity and genotoxicity of PAH-contaminated soil from a former manufactured-gas plant site before and after two simulated bioremediation processes: a sequencing batch bioreactor system and a continuous-f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
71
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
6
3

Relationship

3
6

Authors

Journals

citations
Cited by 56 publications
(75 citation statements)
references
References 37 publications
4
71
0
Order By: Relevance
“…26, 27 The soil was treated in a continuously stirred, semi-continuous, slurry-phase (15% w/w) laboratory-scale aerobic bioreactor. Every seven days, 20% of the treated slurry was replaced with a slurry of untreated (feed) soil in a pH 7.5 buffer containing 5-mM phosphate and 2.5-mM ammonium nitrate.…”
Section: Methodsmentioning
confidence: 99%
“…26, 27 The soil was treated in a continuously stirred, semi-continuous, slurry-phase (15% w/w) laboratory-scale aerobic bioreactor. Every seven days, 20% of the treated slurry was replaced with a slurry of untreated (feed) soil in a pH 7.5 buffer containing 5-mM phosphate and 2.5-mM ammonium nitrate.…”
Section: Methodsmentioning
confidence: 99%
“…Polycyclic aromatic hydrocarbons (PAHs) are of human health concern due to their known or suspected genotoxic, mutagenic or carcinogenic effects (Hu et al, 2012). PAHs are mainly derived from anthropogenic activities, such as biomass burning, incomplete fossil fuel combustion, oil spills and some industrial processes .…”
Section: Introductionmentioning
confidence: 99%
“…Weyens et al ( 2013 ) achieved increased accumulation of Cd and toluene by inoculating the willow tree with Cd-resistant, and siderophore-and IAA-producing engineered Burkholderia vietnamiensis BU61 as a donor of the pTOM-TCE plasmid. Hu et al ( 2012 ) reported 84 % PAH removal by the use of genetically engineered higher eukaryotic lines. Sood et al ( 2010 ) developed novel yeast ( Candida digboiensis ) strain that could remove 72 % heneicosane in 8 days at pH 3.0, and 40 mg of eicosane in 50 ml minimal salts medium in 10 days.…”
Section: Transgenic Plants and Microbesmentioning
confidence: 99%